What promotes smartphone-based mobile commerce? Mobile-specific and self-service characteristics. Issue 1 (6th February 2018) - Choi, Sujeong
Abstract : Purpose: Given that smartphones are widely used as a key means for mobile commerce, the purpose of this paper is to provide in-depth understanding of determinants of the utilitarian value that customers seek to obtain from using smartphone-based mobile commerce. Drawing on the technology acceptance model (TAM), the study proposes that usefulness and ease of use are two typical factors representing utilitarian value and verifies their impacts on smartphone-based m-commerce use. Moreover, the paper expands the TAM by considering mobile-specific characteristics (i.e. service ubiquity and location-based service (LBS)) and a self-service technology (SST) characteristic (i.e. user control) as determinants of utilitarian value. Design/methodology/approach: The study entailed conducting a survey, and analyses were conducted based on a total of 379 responses from undergraduate and graduate students who had experience using smartphones for mobile commerce. The analyses used structural equation modeling to test the research model and hypotheses. Findings: First, in the context of the various technologies-involved m-commerce, TAM serves as a theoretical lens to predict user behavior. Second, usefulness is greatly increased by service ubiquity, LBS, and user control. Third, ease of use is enhanced by service ubiquity and user control. Finally, ease of use is a determinant of usefulness. Originality/value: The findings imply that mobile-specific and SST characteristics are the key determinants of utilitarian value in performance-oriented mobile commerce, and utilitarian value is a key determinant of smartphone-based mobile commerce use.